The creative self psychoanalysis, teaching and learning in the classroom - Bibby, Tamara (London Routledge, 2018)
"The Creative Self engages with the work of the psychoanalyst D.W. Winnicott to develop alternative ways of thinking about key issues at the heart of pedagogy; specifically pedagogic relationships, creativity, defiance and compliance. These issues underpin the desires and defences of professionals located in educational institutions, such as the desire to know what is best, to know how to reach all learners, normalised expectations of behaviours and outcomes, and sometimes challenging engagements with students and the curriculum."--Provided by publisher
Includes bibliographical references.
Keywords: Winnicott, D.W. -- 1896-1971 -- Influence; Psychoanalysis and education; Reflective teaching; Teachers -- Psychology; Learning, Psychology of